Incidental Detection of HbQ-India during Beta-Thalassemia Screening - Iyer, Sandhya; Sakhare, Suhas; Sengupta, Caesar; Velumani, A. (Asian Journal of Biological and Life Sciences, 2015)
HbQ-India is a relatively rare hemoglobin variant seen particularly in the Indian subcontinent. In this report we present twenty cases of HbQ-India variant and two cases of HbQ India/Beta- Thalassemia detected in our lab during thalassemia screening tests conducted in camps along with family studies of few cases. These cases were detected over a span of three months from samples screened for thalassemia. In order to perform familial studies, sample of family members of six cases were collected totaling to twenty-two affected cases. Molecular confirmation of the detected HbQ-India trait was done using PCR-ARMS technology. Our study detected frequency of HbQ-India carriers at 1.47%.
Keywords: Frequency; HbQ-India; Hemoglobinopathy